International Brigade. British Battalion : trade unionist members (list) (1938)
1938 034-0094-002 C.F. Casey. 45 Springfield Lane, Ipswich, Guild of Insurance Clerks 6 years. R. Cohen. 43 Dunk St, E.1., N.U.D.A.W. 1 year 6 months. J.A. Moore. 210 Chatswath Ave, Portsmouth, T.&.G.W.U. 3 years. P. O'Halloran. 111 Guilbert House, S.E.8., E.T.U. & T.&.G.W.U. G.H. Parkes. 37 St. Margarets Ave, Levenshulme M/C. N.U.R. Hammersmith 6. W. Ray. 32 Royal Hill, S.E. T.&.G.W.U. E. Smith. 87 The Grampians, Shepherds Bush, W.6. A.S.W. H. Thorne. 30 Idminster Square, Worcester Park, Surrey. A.S.W A. Trawber. 3 Dunbridge Place, Bethnal Green, E.2. L.T.U. 3 years . W. Hewlett. 13 Henry St, Edinburgh, N.U.S. 10 years. J. McKeefrey. 138 Kinton St, Glasgow, S.W.1. N.A.B.T.U. J. Hegarty. 9 Alexandra Place, Rochdule, T.&.G.W.U. 3½ yrs. E. McHale. Manchester, T.&.G.W.U. 4 years. R. Stubbs. 16 Rotherly Rd, Sharston Mount, Wythenshaw, A.E.U. J. Oliver. 16 Woodfield St, Blackwood, Mon. S.W.M.F. E. Price. S. Wales, S.W.M.F. W. Rogers. 15 Off. Grenddi, Rhos, Wrexham, Plasterers TU 1 yr. R. Stickler. 212 Corporation Rd, Grangetown, Cardiff. A.E.U. J. Adderly. Leicester. Dyers Union. C. Broadbent. 20 Raeburns Lodge Terrace, Dewsbury. T.&.G.W.U. 1 year 6 months. G. Burton. 6 Ethel Road Fratton. S.A.U. 8 years. P. Duff. 66 Monastervoice Rd, Crumblin, Dublin, I.T.G.W.U. A.J. Hobbs. Pleasant View, Danbury, Chelmsford, A.E.U. 292/946/34/94(ii)